2014
DOI: 10.1080/07399332.2014.943837
|View full text |Cite
|
Sign up to set email alerts
|

Mothering in the Wake of Childhood Violence Experiences: Reweaving a Self and a World at the Intersection of History and Context

Abstract: We examined the stories of 12 women mothering growing children at the intersection of personal history (childhood violence experiences) and symbolic, structural, and ideological forces and conditions. Women revealed their determination to reweave a self and a world, that is, to continually reconstruct and reconfigure their lives to change the story for themselves and their children. Women's ability to reweave, however, was facilitated or challenged through intersections with family, networks, single stories, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Transition to parenthood marks a time in a survivor’s life when they themselves are increasingly vulnerable (distress in pregnancy, fear, disempowered in care) and new fears for the safety of their child are exposed. At the same time, pregnancy is often a catalyst for seeking help and an opportunity for healing, to moving forward and making sense, and to “reweaving” a future as described by Pitre [75]. This analytic theme incorporates four descriptive subthemes of: Distress symptoms , including fear and lack of trust ; coping strategies ; factors that help recovery , growth and healing ; and the healing journey though pregnancy , birth and parenting .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition to parenthood marks a time in a survivor’s life when they themselves are increasingly vulnerable (distress in pregnancy, fear, disempowered in care) and new fears for the safety of their child are exposed. At the same time, pregnancy is often a catalyst for seeking help and an opportunity for healing, to moving forward and making sense, and to “reweaving” a future as described by Pitre [75]. This analytic theme incorporates four descriptive subthemes of: Distress symptoms , including fear and lack of trust ; coping strategies ; factors that help recovery , growth and healing ; and the healing journey though pregnancy , birth and parenting .…”
Section: Resultsmentioning
confidence: 99%
“…In Australia, Atkinson et al [92, 93] propose an ‘educaring approach’ that combines compassionate care and deep listening with gentle ‘education’, to help people understand and make meaning of their trauma experiences, and find ways to heal or ‘reweave’ a future. This analogy of ‘reweaving’ was developed by Pitre [75] and refers to a process of reconstructing self and a world that is safe while mothering with a background of childhood violence. Pitre [75] argues that many clinical routines and practices appear to meet professional need rather than provide the individualised support that is required and reinforce rigid and unhelpful misconceptions of what it means to be a ‘good’ mother.…”
Section: Discussionmentioning
confidence: 99%
“…We mainly focused on the exploration of facilitating and constraining rules, routines, expectations, ideologies, and practices to highlight forces and conditions shaping family members' everyday life. Through these salient concepts we also were able to explicate the mechanisms underpinning their efforts to meaningfully influence circumstances in view of, or in spite of, the pressures to conform and maintain status quo within their family (Kushner, ; Pitre, Kushner, Hegadoren & Raine, in press; Pitre, Kushner, Raine, & Hegadoren, ). The complementary perspectives of both feminist intersectionality and critical theory directed our attention to relations of power, oppression, and domination.…”
Section: The Contribution Of Theoretical Triangulation In Family Resementioning
confidence: 99%
“…Each multifaceted composite story will include the voice of multiple social actors, as exact excerpts of their stories are provided to explain a particular facet of an experience from various positions. 47,48 Ultimately, these composite stories re-present social actors' experiences of personal strengths and encountered challenges as they strive for agency, reflexivity, voice, and identity in the face of multiple and various adverse conditions. 47,48 In addition, these composite stories include their implicit and explicit recommendations for social change.…”
Section: From Analysis To Interpretationmentioning
confidence: 99%
“…Ultimately, we were able to recognize and expose a number of intersecting axes of oppression 31,32 fostering health inequities and social injustice 31,35 in the lives of our participants and to depict the ways that these influenced their choices and decisions. 47,48 We anticipate that our approach to theoretically triangulated critical feminist narrative inquiry will evolve as opportunities arise for further refinements, discussions, and critique. For now, we have found that the stories that were shared by participants were a powerful means to bring to light personal and collective strengths and challenges as well as experiences of health inequities and social injustice.…”
Section: Narrative Inquiry With a View Toward Social Justicementioning
confidence: 99%